Readings in human-computer interaction : toward the year 2000 - Baecker, Ronald M. (Interactive Technologies., 1995)
The effectiveness of the user-computer interface has become increasingly important as computer systems have become useful tools for persons not trained in computer science. In fact, the interface is often the most important factor in the success or failure of any computer system. Dealing with the numerous subtly interrelated issues and technical, behavioral, and aesthetic considerations consumes a large and increasing share of development time and a corresponding percentage of the total code for any given application. A revision of one of the most successful books on human-computer interaction, this compilation gives students, researchers, and practitioners an overview of the significant concepts and results in the field and a comprehensive guide to the research literature.